1991
DOI: 10.1021/jm00108a017
|View full text |Cite
|
Sign up to set email alerts
|

Function of negative charge in the "address domain" of deltorphins

Abstract: Deltorphins A, B, and C exhibit high delta-affinities (Ki = 0.12-0.31 nM) and very high delta-receptor binding selectivities (Ki mu/Ki delta = 1800-4100). A study of the delta-receptor binding properties of 15 deltorphin analogues focused primarily on the influence of the anionic group in the C-terminal tetrapeptide. Amidation of the beta-carboxyl groups of [Asp7], [Glu4], or [Asp4] in deltorphins A, B, and C, respectively, yielded peptides with enhanced mu-receptor affinities and minor changes in delta-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 8 publications
3
86
0
Order By: Relevance
“…5,10,16 The present data indicate that the loss of backbone flexibility imposed by the bulky glycosylated Thr 4 in DER and DEL C peptides may presumably limit the opioid binding. 16 The binding properties for µ-and δ-opioid receptors for all of glycopeptides were consistent with the biological activity as tested by GPI and RJ bioassays.…”
Section: Resultsmentioning
confidence: 65%
“…5,10,16 The present data indicate that the loss of backbone flexibility imposed by the bulky glycosylated Thr 4 in DER and DEL C peptides may presumably limit the opioid binding. 16 The binding properties for µ-and δ-opioid receptors for all of glycopeptides were consistent with the biological activity as tested by GPI and RJ bioassays.…”
Section: Resultsmentioning
confidence: 65%
“…In fact, the reversed polarity of peptide [8] further demonstrated that the D-configuration in the N-terminal tripeptide was important for the binding mechanism. Of these residues, Pro 2 [11,12,16] and Phe 3 [9] appear to be quite essential: Their D-isomers dramatically reduced affinity. Furthermore the antipode of compound 9 demonstrated the requirement for the simultaneous L-configuration for both Tyr 1 and Pro 2 [10,14].…”
Section: Resultsmentioning
confidence: 99%
“…Opioid receptor affinities were determined under equilibrium conditions [2.5 h room temperature (23 °C)] in competition assays using brain P 2 synaptosomal membranes prepared from Sprague-Dawley rats 40, 41. Synaptosomes were preincubated to remove endogenous opioid peptides and stored at −80 °C in buffered 20% glycerol 40, 42.…”
Section: Methodsmentioning
confidence: 99%